Occult Breast Cancer - Kul, Aslihan; Taşgın, Ahmet Aydin; Soylemez, Tuce; Baysal, Begumhan; Baysal, Hakan; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2018)
Today breast cancer is the most common cancer type in women, in both developed and developing countries. However, occult breast cancer is a highly rare type in all breast cancers. For the first time in history to know, Halsted defined the term “occult breast cancer” with 2 cases of his’ in the journal, Annals of Surgery. We have 2 similar cases who were 52 and 61-years-old patients and presented our clinic with left axillary swelling and pain. On physical examination and with imaging techniques there wasn’t any primary lesion found. Examination of lymph nodes’ biopsy material was compatible with breast cancer metastasis for both of the patients and they were diagnosed with occult breast cancer. They underwent a modified radical mastectomy surgery and axillary curettage. Histopathologic examination of the excised breast material revealed T1 invasive breast cancer. International Journal of Human and Health Sciences Vol. 02 No. 04 October’18. Page : 239-243